Perancangan Bangun Game Edukasi Sejarah Kemerdekaan Indonesia Menggunakan Model Waterfall Berbasis Android (Studi Kasus Smk Roudhotssallam) - Ahmad Rizal; Joko Suwarno (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract The advancement of information technology has opened new opportunities in educational approaches. One innovative approach involves leveraging mobile devices, such as Android-based devices, to facilitate interactive learning. The objective of this research is to design and develop an Android-based educational game focusing on Indonesian independence history, particularly tailored for SMK Roudhotssallam students. This study adopts the Waterfall software development model, encompassing phases of requirements analysis, design, implementation, testing, and maintenance. During the requirements analysis phase, an initial survey was conducted to identify students' preferences concerning game content, user interface, and features. Subsequently, in the design phase, visual design, level design, and interaction mechanisms were crafted in line with the Indonesian independence history material. Game development took place during the implementation phase, employing programming languages and the Android Studio platform. Historical material is presented through challenges, puzzles, and quizzes related to significant events during the Indonesian independence struggle. In the testing phase, the game was evaluated by SMK Roudhotssallam students to measure the suitability, attractiveness, and educational effectiveness of the developed game. The outcome of this research is an engaging and interactive educational game that aids students in comprehending Indonesian independence history in a more captivating manner. Keywords: Educational Game, Indonesian Independence History, Waterfall Model, Android, SMK Roudhotssallam.